Barometr koniunktury dla rolnictwa w Polsce - Idzik, Marcin (Composite Leading Indicators of Business Activity for Agriculture Sector in Poland, 2005)
The author presents composite leading indicators of business activity for agriculture sector, compiled according to the OECD methodology. First part of the paper examines the amplitude of growth cycles observed in the development of the economy in the period of 1975-2002. The second part presents composite leading indicators for agriculture. All are well correlated with the reference cycle, but they display very short leads if any. Nonetheless, the barometer may be useful in monitoring cyclical developments in the economy.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 337-341